NUMERICAL ANALYSIS OF GAS-DROPLET CHEMICAL PLUG-FLOW REACTOR OPERATING MODES - Valeria V. Pritchina; Victor N. Pushkin; Rudolf A. Neydorf (Advanced Engineering Research)
A one-dimensional model and numerical solution of the non-stationary modes of the adiabatic gas-droplet chemical plug-flow reactor are considered. The developed approach permits to investigate processes of heat and mass transfer in the laminar flow of the reacting gas mixture with hydrocarbon fuels droplets. It may be useful for hazard operability.